Effect of Fucusvesiculosus Algae on the Growth of Some Types of Fungi Isolated from the Mouth of Children with Oral Thrush Lesion - Zahraa Ali; Meethaq S. Abood (Indian Journal of Forensic Medicine & Toxicology, 2021)
Oral swab samples were collected from 120 children(ages between new born and 12 years). Samples werecollected from the pediatric department of Al-Rifai General HospitalAnd Al-Shatrah General Hospital andMuhammad Al-Mousawi Children’s Hospital in Nasiriyah For the period from 24/2/2020 to 7/5/2020.Thenumber of samples that are positive for culture80 samples at a percentage of 66.67% Males 60% and females40% ,Then, this study show that there were Four types of Candida. They are Candidaalbicans,C.krusei,C.parapsilosis ,C.tropicalis .C. albicans was the most common type, with a percentage of 77.5%.The resultsof the study showed that the highest incidence of oral thrush was among newborns. Whose age was less thanone year, and the incidence of this disease was among this age group. % 83.75.The study included testingthe inhibitory efficacy of the aqueous and alcoholic extracts of FucusvesiculosusAgainst four species, allbelonging to the genus Candida, using the Agar well Diffusion Method.It was found that the alcoholicextract better than aqueous extract in effect on the isolated yeasts.